ANALISIS PEMANFAATAN PERPUSTAKAAN SEKOLAH DALAM MEMBANGUN BUDAYA MEMBACA DI SDN GAYAM 3 - Wahyu Ning Tiyas; Novi Nitya Santi; Wahid Ibnu Zaman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problems studied in this thesis are: Analysis of library utilization in building a reading culture of students at SDN Gayam 3. The purpose of this study is to find out various student activities in the school library, to find out the library program in building a reading culture of students, and to find out an overview of the use of school libraries. To discuss the problems studied, the author uses a qualitative approach with a case study research type. The subjects of this study were the principal, students, head of the library, and teachers at SDN Gayam 3. This research was conducted on May 15-17, 2024. The data collection techniques used were observation, documentation, and interviews. The validity test of the data used extended observation, increased research accuracy, and triangulation of data sources, technical triangulation, and time triangulation, and the results of the study showed several findings, namely the background of the use of the library in improving students' reading culture in the SDN Gayam 3 library. Based on the results of observations, interviews, and documentation conducted in the field with the principal, students, and the head of the library, it showed that the SDN Gayam 3 library played a significant role in improving students' reading culture, but there were several library roles that had not been fully implemented.